DESIGN AND TEST OF CONNECTING POINT BETWEEN ACRYLIC SPHERE AND STAINLESS STEEL TRUSS FOR JUNO CENTRAL DETECTOR - HAO JiaJun; QIAN XiaoHui; MA XiaoYan; HENG YueKun; WANG LingShu; WANG YuanQing (Jixie qiangdu, 2016)
The structure of connecting point between a large acrylic sphere and stainless steel truss outside was designed preliminarily,and its loading capacity was verified by finite element method using ABAQUS software. Multiple nonlinear problems involved in the FE model was simulated,and stress under different boundary conditions was compared. But results of loading experiment of preliminary structure did not reach expectations. Then preliminary structure of connecting point is improved,in accordance with the result of loading experiment,and loading capacity of improved structure was verified. Finally,testing results of loading experiment of improved structure was in line with expectations and met well with results of FEA.